Test-driven development for Android : LiveLessons - Shum, Cassie; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2017)
"In Test-Driven Development (TDD) for Android, ThoughtWorks lead consultant Cassie Shum takes a deep dive into the critical role of TDD in mobile development. This video quickly reviews Continuous Delivery best practices and the role of CD in mobile development. The video then focuses on the role of TDD, showcasing how to use tools for unit testing and UI testing by demonstrating with Android testing frameworks Robolectric and Espresso."--Resource description page.
Presenter, Cassie Shum.
Title from title screen (viewed August 24, 2016).
Keywords: Android (Electronic resource); Mobile apps; Application software -- Development; Electronic books